Rogier van der Weyden and stone sculpture in Brussels - Fransen, Bart 1973- (Distinguished contributions to the study of the arts in the Burgundian Netherlands, 2013)
Rogier van der Weyden's painted oeuvre has been the subject of many publications. But his artistic activities were much wider in scope. With its focus on stone sculpture in Brussels at the time that Rogier was working there, an area of art history that to date has been little studied, this book offers a fresh and fascinating look at the context in which Brussels's famous city painter worked. Exploring the complex network of stoneworkers and craftsmen, from the stone quarry to the sculptor's workshop, the raw material to the finished work, Bart Fransen discovers a number of remarkable but hitherto unknown or misjudged sculptures now in churches, an abbey, a béguinage, a museum's reserve collection and a castle chapel. With these various case studies in mind he examines Rogier van der Weyden's direct involvement in sculptural projects, drawing on the evidence revealed by archive documents, drawings and the sculptures themselves